Four new species of the Mesolycus ilyai species group (Coleoptera: Lycidae) from China - Du, Ruo-Lan; Yang, Yu-Xia; Yang, Xing-Ke; Liu, Hao-Yu (Zootaxa, 2024)
Four new species of the Mesolycus ilyai species group are described from China, namely, M. baoi sp. nov., M. latidentatus sp. nov., M. hainanensis sp. nov. and M. clausus sp. nov. The generic diagnosis of Mesolycus is summarized; and an identification key and a distribution map of the M. ilyai species group in the world is updated.